Comportamento e ecologia reprodutiva de Leptodactylus Mystacinus (Burmeister 1861) (Anura, Leptodactylidae) em áreas de cerrado - Oliveira Filho, Júlio César de (2005)
In the present work we describe aspects of the reproduction of Leptodactylus mystacinus. We conducted the work in Uberlândia (MG, Brazil). We followed the reproductive activities of the species in the field weekly from October to March (2005) and determined the daily pattern of calling activity. We recorded calls with a digital recorder (44100 Hz, 16 bit). We estimated the offspring number by counting eggs or early tadpoles(< 15 mm) in egg clutches and determined if the tadpoles were able to generate foam. The females are larger than males; males have a shovel shaped nose and generally the darker chin. The males started calling after the fírst rains and stopped in mid March. In October the calling activities started one hour before sun down and extended to the fírst hours of the next day. The reproduction took place mainly in pond margins. The egg clutches were found in underground chambers, which were excavated by males. During the court a female approaches a calling male and is led to the chamber. When around the chamber, the male entered fírst. The male could to excavate the chamber while courting. Egg clutches followed in the fíeld were not guarded by any parental the days after egg-laying. We found adults in chambers close the egg clutches. The underground chamber is nearly spherical and has an entrance tunnel. During agonistic interactions male emitted territorial call, could beat the hands and/or feet in the ground and fíght. The advertisement call is a single note released around 213 times/min., has one harmonic, the dominant frequency is the same that of the fundamental with a energy peak in 2239 Hz; lasts around 0.04 s, call intervals around 0.18 s. The courtship call is a single note, released 258 times/min., has a single harmonic with the dominant frequency coincident with the fundamental, with energy peaking around 2928 Hz; has a rising modulation from the beginning to the middle and descending from this point; lasts 0.04 s, call intervals around 0.24 s. The territorial call is a single note released 246 timer/min.; has two harmonics, the fírst in 2067 Hz, the fundamental frequency is coincident with the dominant, the second is between 3643-3790 Hz; has descending modulation and lasts 0.04 s, intervals around 0.09 s. In 15 days within the chamber the tadpoles presented little yolk and reached stage 27 (11.6 mm TL); close the metamorphosis reached 49 mm TL. Once within a pond the tadpoles spent 13 days to complete metamorphosis. The offspring number in egg clutches varied from 159 to 627.The eggs were yellow and measured around 4.1 mm in diameter. The tadpoles were able to generate foam, which were produced by releasing bubbles through the mouth. In southeastern Brazil, the reproductive season of the species ends in March, before the ending of the rain season, what may allow to the individuais accumulated reserves in order to cross dry season. The chambers of the species were larger then that of L. fuscus, but were similar in shape by presenting the entrance tunnel. Our data suggests that the parental care behavior is facultative in the species and not as frequent as that described to some populations of L. fuscus. Differently of L. fuscus, L. furnarius and Leptodactylus sp., males L. mystacinus can dig the chamber while courting. The behavior of beating the hands or feet on the ground may generate seismic signals to communication, as already described to L. albilabris, but may also represent some sort of visual display. Male-male agonistic interactions involving vocalizations and fíghts were also described to other species of Leptodactylus. The tadpoles were able to generate foam releasing bubbles through mouth, as in other species of the Leptodactylus of the Leptodactylus fuscus group and in L. labyrithicus. This production of foam may avoid compaction of the tadpoles on the bottom of the chamber and assists in gas exchanges and excretion. Keywords: habitat, vocalizations, courtship, territoriality, parental care, courtship call, territorial call, foam nest, underground chamber, egg number, seasonality, tadpoles.